Leadership Tips for Department Chairs: From Theory to (Best) Practice - John Griffith (Academic Chairpersons Conference Proceedings, 2020)
This presentation will discuss tips and best practices that effective leaders use in working with and motivating faculty and staff. Good leaders are rare but most of us can lead effectively if we understand how to negotiate the mission/people balance in our organization.
Keywords: education leadership; motivation; supervision; department chair; productivity